Answer:
7x(-4x+5)
Multiplying: -56+35x
Explanation:
![\mathrm{Factor\:assuming\:x\ge-\\\infty}\\\:a^(b+c)=a^ba^c\\x^2 = xx\\-28xx+35x\\-7 * 4xx + 7 * 5x\\=7x\left(-4x+5\right)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ofda0q0s60s2s0xchjr9q0v2xilnj4lqcd.png)
The only reason I had to assume x was any negative number was so that the absolute value did not matter in this instance, therefore making x become a negative number.
The other result, however, came from this:
![-28\cdot \:2=-56\\=-56+35x](https://img.qammunity.org/2023/formulas/mathematics/high-school/7ktrumun4xw35gejwspi8luxizc2tzdal2.png)
Inform me of any concerns. Hope this helps.